A Method to Estimate the Population Level of Aceria litchii (Prostigmata: Eriophyidae) and a Study of the Population Dynamics of This Species and Its Predators on Litchi Trees in Southern Brazil - De Azevedo, Leticia Henrique [UNESP]; Maeda, Enzo Yuji; Inomoto, Mario Massayuki; De Moraes, Gilberto Jose (Entomological Soc Amer, 2014)
Litchi (Litchi chinensis Sonnerat) is native to Southeast Asia, where most of the world cultivation of this crop is done. Its commercial cultivation in Brazil is recent and concentrated in the state of Sao Paulo. This crop has been severely damaged in Asia and Brazil by the litchi erineum mite, Aceria litchii (Keifer) (Eriophyidae). The objectives of this study were the adaptation of a method to estimate the density of A. litchii, an evaluation of the population dynamics of this pest and of its associated predators in the state of Sao Paulo, and an estimation of its injury levels to litchi trees. To estimate the density of A. litchii, an adaptation of a method commonly used to evaluate nematode densities in plant roots was performed. This method was shown to be adequate for the estimation of the number of A. litchii, and it might also be useful for similar evaluations of other erineum forming mites. Field samples to determine the pest population dynamics were collected monthly from August 2011 to July 2012. Sampled leaves were examined under a stereomicroscope for removal of predators and subsequent extraction of A. litchii by the adapted method. A. litchii reached maximum densities in November 2011 and June 2012, being found at low densities between January and March 2012. The pattern of variation of A. litchii injury levels was similar to that of the density of A. litchii. The main predatory mite co-occurring with A. litchii was the phytoseiid Phytoseius intermedius Evans and McFarlane. However, high injury levels due to A. litchii suggest that the predator was unable to prevent visible damages to the trees, indicating that control activities should be adopted by growers.
Keywords: ecology; pest mite; Phytoseiidae